Nitrogen doses and splitting in top dressing in the production, quality, and macronutrients content in zucchini (Cucurbita pepo) seeds - Tavares, Ana Emília Barbosa (2021)
Despite the importance of the nutrients, mainly nitrogen, in the formation and chemical composition of the seeds, little research has been done to verify the relationship between the nutrients supplied to the plants and the quality of the seeds produced. The objective of this study was to evaluate the influence of nitrogen doses and splitting on yield, quality and macronutrients content in zucchini seeds. Two experiments (crop 2014 and crop 2015) were installed, with thirteen treatments in the factorial scheme 4x3+1, with four nitrogen doses in top dressing (62.5; 125.0; 187.5; 250.0 kg ha-1), three splitting (1/6+1/3+1/2; 1/4+1/2+1/4; 1/3+1/3+1/3 of total dose in each split), and one treatment without N fertilization in top dressing (dose 0), with four replications. Seed production and quality and macronutrient content in seeds were evaluated. There wasn’t significant effect on number of fruits and seeds produced per plant. However, in crop 2014 the higher the doses of N in top dressing, the higher the seed weight per fruit and per plant, the weight of 100 seeds and the vigor (first count in germination test). In crop 2015, seeds with the best quality (germination and first counting) were obtained in the 1/4+1/2+1/4 splitting. The decreasing order of the macronutrient content in the seeds was N>P>K>Mg>S>Ca.